Discovery of AZD-2098 and AZD-1678, two potent and bioavailable CCR4 receptor antagonists - Kindon, Nicholas; Andrews, Glen; Baxter, Andrew; Cheshire, David; Hemsley, Paul; Johnson, Timothy; Liu, Yu-Zhen; McGinnity, Dermot; McHale, Mark; Mete, Antonio; Reuberson, James; Roberts, Bryan; et al. (American Chemical Society, 2017)
N-(5-Bromo-3-methoxypyrazin-2-yl)-5-chlorothiophene-2-sulfonamide 1 was identified as a hit in a CCR4 receptor antagonist high throughput screen (HTS) of a sub-set of the AstraZeneca compound bank. As a hit with a lead-like profile, it was an excellent starting point for a CCR4 receptor antagonist program and enabled the rapid progression through the Lead Identification and Lead Optimization phases resulting in the discovery of two bioavailable CCR4 receptor antagonist candidate drugs.